2011
DOI: 10.1088/0031-9155/56/16/004
|View full text |Cite
|
Sign up to set email alerts
|

Variability of a peripheral dose among various linac geometries for second cancer risk assessment

Abstract: Second cancer risk assessment for radiotherapy is controversial due to the large uncertainties of the dose-response relationship. This could be improved by a better assessment of the peripheral doses to healthy organs in future epidemiological studies. In this framework, we developed a simple Monte Carlo (MC) model of the Siemens Primus 6 MV linac for both open and wedged fields that we then validated with dose profiles measured in a water tank up to 30 cm from the central axis. The differences between the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…Beyond 3.75 cm from the field edge, discrepancies were about 40% and could be up to 55% for the furthest points (11.25 cm in this study). In a similar comparison, Joosten et al [44] found differences of up to 179% for points within 10 cm from the beam edge of a small field size (5 cm×5 cm) when comparing the dose calculated with the TPS CMS XiO (version 4.60, Elekta, Crawley, UK), using a point kernel-based algorithm, and the dose measured with a 0.13 cm 3 ionisation chamber (IC10, Scanditronix Wellhofer GmbH, Schwarzenbruck, Germany).…”
Section: Estimation Of the Dose At The Point Or Volume Of Interestmentioning
confidence: 70%
See 2 more Smart Citations
“…Beyond 3.75 cm from the field edge, discrepancies were about 40% and could be up to 55% for the furthest points (11.25 cm in this study). In a similar comparison, Joosten et al [44] found differences of up to 179% for points within 10 cm from the beam edge of a small field size (5 cm×5 cm) when comparing the dose calculated with the TPS CMS XiO (version 4.60, Elekta, Crawley, UK), using a point kernel-based algorithm, and the dose measured with a 0.13 cm 3 ionisation chamber (IC10, Scanditronix Wellhofer GmbH, Schwarzenbruck, Germany).…”
Section: Estimation Of the Dose At The Point Or Volume Of Interestmentioning
confidence: 70%
“…The main algorithms available in present clinical TPSs [55] are measurement-based [56,57] and model-based algorithms [58][59][60][61][62][63][64]. However, TPSs are not designed to evaluate the dose in the regions of the patient's body outside the treatment beams [44,[65][66][67][68][69][70][71][72][73][74][75]. This has led medical physicists to develop in-house algorithms for estimating out-of-field doses.…”
Section: Estimation Of the Dose At The Point Or Volume Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Our adjustment of the photon dose to voxels below the 5% isodose line led to an average increase in our OAR mean dose by 14.5% in total breast, 2.6% in total lung, 4.6% for the thyroid. Previous papers reported an under dosage by the commercial TPS to voxels which fell below the 5% isodose line by 40 -60% 14,15 .…”
Section: Discussionmentioning
confidence: 96%
“…14,15 Instead, stray doses were determined using supplemental approaches. Specifically, stray radiation doses from photon therapy were calculated following the methodology from Howell et al 16 , which uses an analytical model to predict absorbed dose derived from TLD measurements of a HL IMRT treatment delivered to an anthropomorphic phantom.…”
Section: Stray Radiationmentioning
confidence: 99%